HEATSINK 3D BY CFD ANALYSIS OF COOLING SYSTEM IN A PC DESKTOP - Sulung, Sukma; Mainil, Afdal Kurniawan; Suandi, Agus (UNIB Press, 2019)
Heatsink was analyzed by using CFD to entirely model temperature distribution over VGA. It was set up on two conditions, standby and maximum load. At the standby condition the temperature on the 21 fin was 44.77 °C by CFD and it is comparable to 44.20 °C by direct measurement. While at the maximum load condition the temperature on the 12th fin was 61.78 °C by CFD and it is comparable to 59.80 °C by direct measurement. The simulation error of the analysis was 0,97% - 1,29% of the standby and 3,31% - 3,92% of the maximum load.